KOMUNIKASI TERAPEUTIK PERAWAT DALAM MENINGKATKAN MOTIVASI POLA HIDUP AKTIF DAN SEHAT PADA LANSIA KATEGORI PARSIAL GRIYA WREDA JAMBANGAN SURABAYA - Retno Dewanti, Niken Pramesthi; Tandyonomanu, Danang (Universitas Negeri Surabaya, 2024)
Therapeutic Communication is an interpersonal relationship between the counselor and client. Through this relationship, the counselor and client gain joint learning experiences in order to improve the client's emotional experience. Therapeutic communication is a type of interpersonal communication that is useful for assisting in the process of stimulating and changing behavior carried out by nurses towards patients or clients. Therapeutic communication is usually carried out to change thought patterns which can ultimately influence the patient's activities. Based on the Sustainable Development Goals which have become a world agreement and were drafted by the UN in point number 3, it states